2017
DOI: 10.3390/app7040340
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Propagation Models with Bands of Forbidden Frequencies or Forbidden Wavenumbers: A Consequence of Abandoning the Slowly Varying Envelope Approximation and Taking into Account Higher-Order Dispersion

Abstract: Abstract:We study linear and nonlinear pulse propagation models whose linear dispersion relations present bands of forbidden frequencies or forbidden wavenumbers. These bands are due to the interplay between higher-order dispersion and one of the terms (a second-order derivative with respect to the propagation direction) which appears when we abandon the slowly varying envelope approximation. We show that as a consequence of these forbidden bands, narrow pulses radiate in a novel and peculiar way. We also show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
1
0
4
Order By: Relevance
“…It is to noted that we have also studied the dispersion relation for the system with HEM (Λ = 1) and observed that the range of forbidden frequencies is even more when compared to the system with LEM (Λ = 0.01) albeit they exhibit somewhat different dispersion curves (not shown here). These findings clearly suggest that the considered systems may support some novel kinds of localized states (as the dispersion relation of the present system is having analogy with the cryptographic system [20,21]) which we leave for a detailed subsequent work.…”
Section: Modulational Instability (Mi) Analysismentioning
confidence: 51%
“…It is to noted that we have also studied the dispersion relation for the system with HEM (Λ = 1) and observed that the range of forbidden frequencies is even more when compared to the system with LEM (Λ = 0.01) albeit they exhibit somewhat different dispersion curves (not shown here). These findings clearly suggest that the considered systems may support some novel kinds of localized states (as the dispersion relation of the present system is having analogy with the cryptographic system [20,21]) which we leave for a detailed subsequent work.…”
Section: Modulational Instability (Mi) Analysismentioning
confidence: 51%
“…La propagación de ondas y los modelos no lineales son temas que aparecen en muchísimos sistemas: en el aire [8], en el agua [9], en los sólidos [10] y, de manera particularmente importante, en sistemas no lineales en los cuales puede propagarse la luz [11]. En este trabajo nos interesan los modelos que describen la propagación de pulsos de luz en fibras ópticas.…”
Section: Ecuaciones Con Solitones óPticosunclassified
“…Si examinamos las 5 ecuaciones mencionadas en la sección anterior encontraremos que en esos 5 casos las relaciones de dispersión están dadas por ecuaciones de la forma: Estas curvas son inesperadas. Nunca antes de la publicación de la referencia [20] se habían reportado relaciones de dispersión con estas formas. La curva que se observa en la Fig.…”
Section: úLtimo Teorema De Fermat Y Solitones óPticosunclassified
“…La curva que se observa en la Fig. 2 de [20] es particularmente interesante. De acuerdo a esta curva hay 2 intervalos de frecuencia prohibidos:…”
Section: úLtimo Teorema De Fermat Y Solitones óPticosunclassified
See 1 more Smart Citation